Learning Model Service-Learning at Boarding School - Moch. Sya'roni Hasan (Program Studi Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2021)
This study aims to describelearning learning servicecarried out at Pondok Pesantren Al Urwatul Wutsqo Jombang. This study used a qualitative approach with case study design. Data was collected using in-depth interviews, participatory observation, and documentation. Data analysis techniques include data collection, data condensation, data presentation, and drawing conclusions, checking the validity of the findings by extending participation; source triangulation techniques, theories, and methods; and persistence of observation. Research informants are pesantren caregivers, ustadzah, students and the community. The results showed that: first, the steps of service learning that were applied at Pondok Pesantren al Urwatul Wutsqo Jombang and Darussalam Sumbersari Kediri, among others: 1). Intention, 2). Curriculum integration, 3). Preparation includes; debriefing and selection ofparticipants service learning, determining the place of service-learning service, division of groups and accompanying teachers, departure ofparticipants service learning, 4). Implementation of service learning, 5). Meditation/contemplation, 6). Evaluation of service learning, and 7). Closing of service learning.